2023
DOI: 10.1002/lary.31079
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Imaging and Surgical Findings in Pediatric Frontonasal Dermoids

Shaunak N. Amin,
Jennifer M. Siu,
Patricia L. Purcell
et al.

Abstract: ObjectiveTo review cases of congenital frontonasal dermoids to gain insight into the accuracy of preoperative computed tomography (CT) and magnetic resonance imaging (MRI) in predicting intracranial extension.MethodsThis retrospective study included all patients who underwent primary excision of frontonasal dermoids at an academic children's hospital over a 23‐year period. Preoperative presentation, imaging, and operative findings were reviewed. Receiver operating characteristic (ROC) statistics were generated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Naturally, it is important to determine the degree of dural extension before any type of surgical intervention, which can be seen in 5-45% of lesions [16,21,22]. CT or MRI is recommended to evaluate for intracranial dermoid cyst extension, but there is a debate over which modality, not if both, should be obtained preoperatively [23]. CT may be fast and highlight osseous structures, but there is significant concern for radiation exposure, especially for young children.…”
Section: Nasal Dermoid Cystmentioning
confidence: 99%
See 2 more Smart Citations
“…Naturally, it is important to determine the degree of dural extension before any type of surgical intervention, which can be seen in 5-45% of lesions [16,21,22]. CT or MRI is recommended to evaluate for intracranial dermoid cyst extension, but there is a debate over which modality, not if both, should be obtained preoperatively [23]. CT may be fast and highlight osseous structures, but there is significant concern for radiation exposure, especially for young children.…”
Section: Nasal Dermoid Cystmentioning
confidence: 99%
“…CT may be fast and highlight osseous structures, but there is significant concern for radiation exposure, especially for young children. MRIs negate this concern, but often require sedation and long acquisition times [23]. According to a recent single-institution study comparing the accuracy of CT and MRI in predicting intracranial extension for frontonasal dermoids, the authors demonstrated that the sensitivity and specificity of CT were 87.5% and 97.4%, respectively, whereas MRI was 60.0% and 97.8%, respectively.…”
Section: Nasal Dermoid Cystmentioning
confidence: 99%
See 1 more Smart Citation